Kasus Kopi Mirna Salihin: Sebuah Tinjauan Sosial - Pratyksa, Putu Gede Caka; Purnomo, Hadi (Varied Knowledge Journal, 2024)
The murder of Wayan Mirna Salihin by her friend, Jessica Kumala Wongso, in 2016 was one of the most high-profile criminal cases in Indonesia. The case not only caused deep grief for the victim's family, but also had significant social implications. From a social perspective, the Mirna Salihin kopi case can be analyzed from various aspects, such as Social relations that The case shows that unhealthy social relations can be a trigger for criminal acts. In this case, Jessica is suspected of having a motive of revenge against Mirna because she felt betrayed by her; Gender That the case can also be seen as a form of violence against women. Jessica, as a woman, killed her own friend, who was also a woman. This shows that violence against women can be committed by anyone, including other women. Mass Media that played a key role in shaping public opinion on the case. Sensational and unbalanced media coverage can create negative stigma against Jessica and her family. The Mirna Salihin kopi case is a valuable lesson for Indonesian society. The case shows the importance of maintaining healthy social relations, preventing violence against women, and being wise in consuming information from mass media.